Barriers and enablers to uptake of a contemporary guideline-based management program for hip and knee osteoarthritis: A qualitative study. Issue 4 (December 2020) - Wallis, Jason A.; Ackerman, Ilana N.; Brusco, Natasha K.; Kemp, Joanne L.; Sherwood, James; Young, Kirby; Jennings, Sophie; Trivett, Adrian; Barton, Christian J.
Summary: Objective: To explore barriers and enablers for referral to, and participation in, a contemporary guideline-based osteoarthritis management program – Good Life with osteoArthritis in Denmark (GLA:D Australia ). Design: A qualitative design was used, involving semi-structured interviews with patients with osteoarthritis and medical professionals. Interviews were audiotaped, transcribed verbatim, coded and thematically analysed. Barrier and enabler themes were mapped to the theoretical domains framework and used to inform the development of recommendations for improving uptake of guideline-based osteoarthritis management programs. Results: Twenty patients with hip and/or knee osteoarthritis and 15 medical professionals (5 general practitioners, 4 rheumatologists, 6 orthopaedic surgeons) were included. Across both groups, three themes emerged as barriers (program access; misinformation about osteoarthritis; patient and program factors), one theme emerged as a barrier and enabler (health professional trust, feedback and advice), and two themes emerged as enablers (opportunity to achieve positive outcomes and potentially avoid joint replacement surgery; better program promotion, patient and health professional education, and efficient referral processes). Conclusions: Optimising uptake of guideline-based osteoarthritis management programs requires improved reimbursement models, and better promotion and educational initiatives for patients and medical professionals. A particular focus of education should include dispelling misinformation about osteoarthritis, and highlighting the safety and value of physiotherapist delivered exercise-therapy.